(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article which describes “Characteristics And Main Principles Of Takfir Followers” allows to know more about (introduce with) true face of one more extremistic directions in Islamic World. Core aim of article and direction (purpose) of scientific investigation is a prevention of extremistic and terroristic problems. The article is based on analyzez, synthes, comparation. Along with it based on methodics of hermeneutics and functional-structural analyzez. During the researches there was analyzed that the stream of Takfir is apart from traditional Islamic values ideologic principles are radical. In general stream of Takfir is banned and forbidden to be propaganded in Kazakhstan, but still there is lack of information for explaining about dangeriousparts ofit’s ideology and negative influence to society. This article is usable for religious scholars or for people who are interested in Islamic studies, can be used as a lecture for students and schoolchildren, or a material for seminars. The article can be used to prevent the radicalism and extermalism among the students and the youth. Key words: Islam, Takfir Jamagat, Radicalism, Problems of Prevention of Extremism.